2019
DOI: 10.3390/cryst9050260
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Model and Experimental Investigations on Solution-Mediated Polymorphic Transformation of Theophylline: From Polymorph I to Polymorph II

Abstract: In this work, theophylline was selected as the model compound to study and simulate the solution-mediated polymorphic transformation. The polymorph I and polymorph II of theophylline were prepared and fully characterized. Raman and UV spectra methods were carried out to observe the phase transformation of theophylline from polymorph I to polymorph II at different temperatures. The theoretical models, including dissolution model, nucleation model, and growth model, were established to describe and simulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…All the mentioned peaks of TPH are observed in the spectra of the pure drug and in all the measured time points of the drug-loaded ChewTs, and no variation throughout the stability study could be observed in the prepared dosage form. The absence of a peak at 1329 cm −1 , characteristic to polymorph I, and the presence of the vibrational stretching of C=O at 1662 cm −1 , characteristic to polymorph II in the prepared samples [47], confirms the results found in the FTIR spectra that anhydrous TPH of polymorph II is present in the printed dosage form and that the formulation did not change the TPH polymorph nor were any changes observed over the three-month period.…”
Section: Mechanical Strengthsupporting
confidence: 82%
See 2 more Smart Citations
“…All the mentioned peaks of TPH are observed in the spectra of the pure drug and in all the measured time points of the drug-loaded ChewTs, and no variation throughout the stability study could be observed in the prepared dosage form. The absence of a peak at 1329 cm −1 , characteristic to polymorph I, and the presence of the vibrational stretching of C=O at 1662 cm −1 , characteristic to polymorph II in the prepared samples [47], confirms the results found in the FTIR spectra that anhydrous TPH of polymorph II is present in the printed dosage form and that the formulation did not change the TPH polymorph nor were any changes observed over the three-month period.…”
Section: Mechanical Strengthsupporting
confidence: 82%
“…The FDA recommends a chewable tablet having a hardness of less than 12 kp [49], which corresponds to 118 N. The ChewTs prepared in the current study are in line with this. The melting point of form II has been reported in the literature at 269.1 ± 0.4 • C by Suzuki et al [53] and at around 270 • C by Zhu et al [47]. The anhydrous form I has a higher melting temperature at about 275 • C [47,54].…”
Section: Mechanical Strengthmentioning
confidence: 82%
See 1 more Smart Citation
“…Solvates, a common crystal form in the pharmaceutical industry [1,2], contains active pharmaceutical ingredient (API) molecules and solvent molecules within the crystal structure [3,4], and hydrates are the particular type of solvates with the solvent being water [5]. Solvates might exhibit different physicochemical properties compared with API, such as stability, solubility, dissolution rate, which could affect the bioavailability of pharmaceuticals [6][7][8]. Solvates typically appear during the purification and processing stages of API, such as mixing, wet granulating and spray drying [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphic transformation is frequently encountered in crystallization development. Zhu et al displayed a methodology to understand transformation processes [5]. Probe-based Raman spectroscopy and ATR-FTIR spectroscopy were used to monitor the polymorphic transformation of theophylline in different solvents at different temperatures using a simplified process model that was constructed to fit experimental data.…”
mentioning
confidence: 99%